Synthesis and electrochemical properties of nickel–manganese oxide on MWCNTs/CFP substrate as a supercapacitor electrode. (1st September 2015) - Li, Ya-Hao; Li, Qing-Yu; Wang, Hong-Qiang; Huang, You-Guo; Zhang, Xiao-Hui; Wu, Qiang; Gao, Hong-Quan; Yang, Jian-Hong
Highlights: A 3D conductive MWCNTs/CFP substrate for supercapacitor application is produced. We deposit nickel–manganese oxide on the substrate forming a wonderful electrode. The electrode possesses unique surface morphology and good conductivity. The electrode shows wonderful power characteristics and long-term cycle stability. Abstract: Ultra-small nickel–manganese oxide/multi-wall carbon nanotubes/carbon fiber paper (NMC) composite with 3D porous structure for supercapacitor electrode material was synthesized by an electrochemical deposition process. The MWNCTs depositing on the current collector carbon fiber paper (CFP) via chemical vapor deposition (CVD), as a substrate with high surface to support nickel–manganese oxide, enhance the electrical conductivity of the oxides. These composite was characterized by scanning electron microscope, transmission electron microscope, X-ray powder diffraction and energy-dispersive X-ray spectroscopy. The electrochemical properties of as-prepared composites are also investigated. The results indicate that MWCNTs/CFP composite is a wonderful conductive substrate for supporting metal oxide and NMC possesses wonderful structural and electrochemical properties, which makes NMC a wonderful material for developing supercapacitor electrodes with high electrochemical properties.